1969
DOI: 10.1002/1097-0142(196901)23:1<88::aid-cncr2820230109>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection by immunofluorescenge of antibodies specific for human malignant melanoma cells

Abstract: Cells were separated from tissue specimens of human malignant melanoma and grown in tissue culture on coverslips. After 8 days of growth the explanted cells were fixed and stored until used. Sera from 15 patients with malignant melanoma were reacted with the fixed melanoma cells and a variety of other cells. The indirect immunofluorescence method was used to test for presence of antibodies. Sera from all 15 melanoma patients reacted with fixed melanoma cells giving intense fluorescence of intracytoplasmic gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

1970
1970
1975
1975

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(12 citation statements)
references
References 26 publications
0
9
0
3
Order By: Relevance
“…For instance, Morton et al (1968) described both nuclear and cytoplasmic fluorescence and used nuclear fluorescence as the indicator of reactivity to 3 of their melanomata whereas most other workers have disregarded nuclear fluorescence. The titre of the antibodv detected in the serum has varied from 112 (Muna et al, 1969) to 1/125 (Oettgen et al, 1968). Other variations are seen in the methods used to fix the cells and even the source of the cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Morton et al (1968) described both nuclear and cytoplasmic fluorescence and used nuclear fluorescence as the indicator of reactivity to 3 of their melanomata whereas most other workers have disregarded nuclear fluorescence. The titre of the antibodv detected in the serum has varied from 112 (Muna et al, 1969) to 1/125 (Oettgen et al, 1968). Other variations are seen in the methods used to fix the cells and even the source of the cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Die ersteren werden an fixierten Zellen im indirekten Fluorescenztest beobachtet, sie sind nicht gegen Melanin gerichtet [118,144]. Bei Testungen der Patienten (P)-Seren mit autologen MZ erhielten verschiedene Untersucher [18, 64, 140, 142-t44] in 100% der FNle positive Reaktionen, andere dagegen nut in der iiberwiegenden Anzahl der F/ille [20,59,118,142,143].…”
Section: Introductionunclassified
“…Die cytoplasmatische Fluorescenz verschwindet nach Absorption der Seren mit MZ-Homogenaten [118,140,144,159]. Die Spezifitfit der Untersuchung kann durch negative Tests mit anderen Tumorzellen (nicht M), Fibroblasten, benignen N/ivi und anderen Zellen (z.B.…”
Section: Introductionunclassified
“…Subsequent studies showed that the serum factor was an immunoglobulin and that the effect could be abolished by inactivating complement from the serum (Lewis, Ikonopisov, Nairn, Phillips, Hamilton-Fairley, Bodenham, and Alexander, 1969). Following this, evidence using immunofluorescent techniques indicated the presence of antibody in the serum of non-African patients with malignant melanoma (Lewis et al, 1969;Muna, Marcus, and Smart, 1969). A number of reports also indicated the presence of antibody against components of tumour cells in some other human malignancies and in several animal models using techniques such as cytotoxicity (Hellstrom, Hellstr6m, Pierce, and Bill, 1968;Hellstrom, Hellstrom, Pierce, and Yang, 1968;Arpels and Southam, 1969;Nairn, Nind, Guli, Muller, Rolland, and Minty, 1971), immunofluorescence (Klein, Clifford, Klein, and Stjernward, 1966;Goldstein, Klein, Pearson, and Clifford, 1969;Muna et al, 1969;Nairn et al, 1971), immunodiffusion (McKenna, Sanderson, andBlakemore, 1964;Gold and Freedman, 1965;Gold, 1967;Jehn, Nathanson, Schwartz, and Skinner, 1970), electrophoresis, growth (colony) inhibition (Hellstrom, 1967), and complement fixation (Armstrong, Henle, and Henle, 1966).…”
mentioning
confidence: 99%